Energy Use Efficiency and Economical Analysis in Cotton Production System in an Arid Region: A Case Study for Isfahan Province, Iran - Zahedi, Mortaza; Eshghizadeh, Hamid Reza; Mondani, Farzad (International Journal of Energy Economics and Policy, 2013)
The objective of this survey was to evaluate the energy consumption and the economic analysis of cotton production in Esfahan province of Iran. For this purpose, data were selected from 47 cotton growers using a face-to-face questionnaire. The results indicate that cotton production consumed a total energy of 52507.8 MJ ha-1. Among sources of input energy, the contribution of energy related to diesel fuel (47%) was highest, followed by chemical fertilizers (20%) and water for irrigation (12%). The shares of direct and non renewable energy were 68.3% and 77.7%, respectively. The impacts of indirect and non-renewable energy on cotton yield were higher than those of direct and renewable energy. Energy use efficiency, specific energy, energy productivity, energy intensiveness, and net energy were 0.7, 19.2 MJ-1 kg, 0.10 kg MJ-1, 27.2 MJ-1 $ -1, -15625.2 MJ-1ha-1, respectively. Total cost of cotton production was 1927.9 $ ha-1. About 67% of the cost of production was variable costs, while 33% was fixed costs. The benefit to cost ratio was estimated 1.22. It is suggested that efforts to increase energy efficiency of cotton production in the investigated area should primarily focus on proper use of fertilizers and irrigation systems and also on saving diesel fuel by improving machinery operating performance. Keywords: economical assessment; energy consumption; energy intensiveness; energy productivity JEL Classifications: O13; Q12; Q43